Remark on algorithm 705 A Fortran-77 software package for solving the Sylvester matrix equation AXBT + CXDT = E. - Hopkins, Tim
We present a number of corrections to Algorithm 705 [Gardiner et al. 1992].
Keywords: Software; PROGRAMMING LANGUAGES; Language Classifications; FORTRAN 77.; Mathematical software; Reliability and robustness; Algorithms; Performance; Reliability